2021
DOI: 10.7554/elife.64393
|View full text |Cite
|
Sign up to set email alerts
|

Disparate bone anabolic cues activate bone formation by regulating the rapid lysosomal degradation of sclerostin protein

Abstract: The down regulation of sclerostin in osteocytes mediates bone formation in response to mechanical cues and parathyroid hormone (PTH). To date, the regulation of sclerostin has been attributed exclusively to the transcriptional downregulation of the Sost gene hours after stimulation. Using mouse models and rodent cell lines, we describe the rapid, minutes-scale post-translational degradation of sclerostin protein by the lysosome following mechanical load and PTH. We present a model, integrating both new and est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…8,9 Studies in mice osteocytes and animal models suggest that both transcriptional and posttranscriptional regulation controls sclerostin expression. 10 Rapid changes in sclerostin levels in response to endocrine signals (eg, parathyroid hormone) and mechanical loading may occur as a result of lysosomal degradation of sclerostin protein. 10 These findings illustrate the impact of hormones, biomechanical forces and diet on sclerostin expression in bone and may also influence circulating sclerostin concentrations and expression levels in arteries.…”
Section: Sites and Determinants Of Sclerostin Expressionmentioning
confidence: 99%
“…8,9 Studies in mice osteocytes and animal models suggest that both transcriptional and posttranscriptional regulation controls sclerostin expression. 10 Rapid changes in sclerostin levels in response to endocrine signals (eg, parathyroid hormone) and mechanical loading may occur as a result of lysosomal degradation of sclerostin protein. 10 These findings illustrate the impact of hormones, biomechanical forces and diet on sclerostin expression in bone and may also influence circulating sclerostin concentrations and expression levels in arteries.…”
Section: Sites and Determinants Of Sclerostin Expressionmentioning
confidence: 99%
“…Increased ROS levels and osteogenic gene expression in MC3T3-E1 osteoblasts, through MAPK activation mediated by ROS, were described after stimulation by low-intensity pulsed ultrasounds; inhibition of ROS attenuated osteogenic gene expression, including Runx2, osteocalcin, and osteopontin ( Kaur et al, 2017 ). It is also recognized that osteocytes transduce mechanical load signals to activate Nox2, producing ROS signals; this response is accompanied by a rapid ROS-mediated decrease in sclerostin levels by lysosomes, allowing activation of the Wnt/β-catenin signaling pathway, and bone formation ( Schröder, 2015 ; Gould et al, 2021 ). However, in endothelial cells, oxidative stress due to unregulated Nox activity leads to altered eNOS function, shifting from NO production to O 2 − , further inducing oxidative stress and increasing ROS levels, with subsequent endothelial disfunction ( Meza et al, 2019 ).…”
Section: Oxidative Stress and Bone Mechanobiologymentioning
confidence: 99%
“…Although sclerostin was proven to be a crucial therapeutic target for skeletal diseases, its molecular mechanism of regulation and degradation remains unclear. In addition to transcriptional regulation through the sclerostin gene, a recent report has shown that rapid, minute-scale lysosomal degradation may also be responsible for its down-regulation [ 32 ]. Nevertheless, these results provide strong evidence that the six potential sclerostin-binding inhibitors effectively suppressed the level of both intracellular and extracellular sclerostin.…”
Section: Resultsmentioning
confidence: 99%